QUALITY CONTROL ANALYSIS OF THE RISK OF PAVING PRODUCT DAMAGE USING SIX SIGMA AND KAIZEN METHODS - Iil Islacha; Inggit Marodiyah (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: PT Varia Usaha Beton experienced various problems, including product defects allegedly due to lack of quality control in the production process, and the purpose of this study is to determine the causes of paving product failure and determine the risk reduction strategy for damage to paving products. Method: To conduct this research using six sigma and kaizen methods. Results: January-December 2023, the company standard for product defects was 0.1% of production each month, in January the defect was 0.3%, February the defect was 0.2%, March the defect was 0.5%, April the defect was 0.4%, May the defect was 0.2%, June the defect was 0.3%, July the defect was 0.4%, August the defect was 0.3%, September the defect was 0.4%, October the defect was 0.2%, November the defect was 0.4%, and December the defect was 0.2%, results showed the highest defect was in March 4859 out of 984275 and the lowest was in October 985 out of 552177, and types of defects: crack 9250, gupil 10040, porous 9961, with production improvement analysis using Kaizen Five M Checklist focusing on supervision, machine maintenance, material, SOP, and environment. Novelty: Further research is needed on factors that contribute to product defects.